Peran Kepribadian Hardiness Terhadap Kedisiplinan Belajar Remaja Santri yang Tinggal di Pesantren - Roy Gustaf Tupen Ama; Neni Widyayanti; Oktafia Oktafia (Universitas Al Azhar Indonesia, 2023)
This study aims to determine the relationship between hardiness personality and learning discipline in adolescent students who live in madania Islamic boarding schools. This study uses quantitative methods to analyze using Spearman correlation statistical analysis. Determining the number of samples that the researchers did, using a cluster random sampling technique, namely a cluster sampling technique. The sample in this study was teenage students who lived in the Madania Islamic Boarding School which collected 100 students. The research data was collected using a personality scale of hardiness and a learning discipline scale that was made by the researcher himself. The hardiness personality scale has a valid Cronbach's Alpha 0,918 value and the learning discipline scale has a valid Cronbach's Alpha 0,943 value.Based on the results of statistical tests obtained a positive correlation coefficient (rxy) of 0.772 and a significance level of 0.000 (p <0.01), this indicates that there is a significant positive relationship between personality hardiness and learning discipline. This means that the higher the resilient personality variable will cause the learning discipline variable to increase. The effective contribution given or the contribution of learning hardiness personality with discipline was 59.6%.Keywords - Hardiness Personality, Learning Discipline, Student Youth